Method of Payment and Shareholders Stock Returns: Evidence from Mergers - Jagan Arumugam; Eric H.Y. Koh; Rubi Ahmad (Asian Journal of Business and Accounting, 2026)
Manuscript type: Research paper Research aims: Extant literature has largely focused on how the all-cash and all-stock acquisition payment methods impact shareholders’ returns. It also suggests that the mixed payment method (i.e. various cash-to-stock ratios) is a unique (rather than a hybrid) payment category. Nonetheless, the justification for its uniqueness and the impact of announcing the different ratios remain unclear. This paper aims to fill the gap by examining the effect of the mixed payment method (together with the various constituent cash-to-stock ratios) on acquirer firm shareholders’ returns. Design/Methodology/Approach: This study uses a market model event study on a sample of 305 mergers in the U.S. from 2004 until 2018. Research findings: The key findings are: (1) shareholders reacted negatively to the mixed method of payment announcement by the acquirer firm, and (2) higher cash-to-stock ratios in this method presented higher abnormal stock price returns. Theoretical contribution/Originality: This paper presents a more focused study on how the mixed payment method category (and the different cash-to-stock ratios) impact shareholder returns. Moreover, the twentypercentage- point change criterion used provides granularity in studying the impact. Practitioner/Policy implications: It provides a basis for guiding managers in considering the appropriate cash-to-stock ratio for mixed payment acquisition offers. This would also guide policymakers in state-owned firms on the mixed method of payment offers and to safeguard the shareholders’ interests. Research limitation: The sample is limited to domestic mergers that occurred in the U.S. Future studies may consider including cross-border mergers and expanding the study to other regions.